2022
DOI: 10.1186/s41239-022-00329-7
|View full text |Cite
|
Sign up to set email alerts
|

The more the better? Comparing two SQD-based learning designs in a teacher training on augmented and virtual reality

Abstract: The purpose of this study was to investigate whether a learning design based entirely on the micro level strategies of the Synthesis of Qualitative Data (SQD) model is better suited to promote teachers augmented and virtual reality-related Will, Skill, and Tool (WST) compared to a learning design based less on the SQD model. To this end, we first developed two learning designs that were randomly distributed across two teacher professional development courses. In one course (n = 23), teachers learned according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 65 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…To support teachers in developing these tailored approaches, professional development regarding AI literacy is needed. For such professional development programs, research-based approaches like suggested in the Tell-Show-Enact-Do learning design (Buchner and Hofmann, 2022) based on the Synthesis of Qualitative Data model (Tondeur et al, 2012) might be helpful as a blueprint.…”
Section: Discussion Of Results and Implicationsmentioning
confidence: 99%
“…To support teachers in developing these tailored approaches, professional development regarding AI literacy is needed. For such professional development programs, research-based approaches like suggested in the Tell-Show-Enact-Do learning design (Buchner and Hofmann, 2022) based on the Synthesis of Qualitative Data model (Tondeur et al, 2012) might be helpful as a blueprint.…”
Section: Discussion Of Results and Implicationsmentioning
confidence: 99%
“…As many studies highlight, the use of XR technology alone does not necessarily improve learning outcomes, and the integration of XR into the teaching space is complex (Huang et al, 2019;Mulders et al, 2020;Southgate et al, 2019). Effective use of an innovative educational training solution depends on multiple factors, including the connection to curriculum design, learning outcomes and the students' needs, the willingness and ability of teaching staff to implement the solution, as well as the ease of technology integration into existing teaching context (Buchner & Hofmann, 2022;Proserpio & Gioia, 2007;Rogers, 2003;Seufert et al, 2021;Straub, 2009). These intricacies associated with the use and uptake of a new technology and teaching modality are likely contributing to the fact that XR technology as a sustainably integrated teaching resource remains in its relative infancy.…”
Section: Introductionmentioning
confidence: 99%